Once-per-week selinexor, bortezomib, and dexamethasone versus twice-per-week bortezomib and dexamethasone in patients with multiple myeloma (BOSTON): a randomised, open-label, phase 3 trial. Issue 10262 (14th November 2020) - Grosicki, Sebastian; Simonova, Maryana; Spicka, Ivan; Pour, Ludek; Kriachok, Iryrna; Gavriatopoulou, Maria; Pylypenko, Halyna; Auner, Holger W; Leleu, Xavier; Doronin, Vadim; Usenko, Ganna; Bahlis, Nizar J; et al.
Summary: Background: Selinexor combined with dexamethasone has shown activity in patients with heavily pre-treated multiple myeloma. In a phase 1b/2 study, the combination of oral selinexor with bortezomib (a proteasome inhibitor) and dexamethasone induced high response rates with low rates of peripheral neuropathy, the main dose-limiting toxicity of bortezomib. We aimed to evaluate the clinical benefit of weekly selinexor, bortezomib, and dexamethasone versus standard bortezomib and dexamethasone in patients with previously treated multiple myeloma. Methods: This phase 3, randomised, open-label trial was done at 123 sites in 21 countries. Patients aged 18 years or older, who had multiple myeloma, and who had previously been treated with one to three lines of therapy, including proteasome inhibitors, were randomly allocated (1:1) to receive selinexor (100 mg once per week), bortezomib (1·3 mg/m 2 once per week), and dexamethasone (20 mg twice per week), or bortezomib (1·3 mg/m 2 twice per week for the first 24 weeks and once per week thereafter) and dexamethasone (20 mg four times per week for the first 24 weeks and twice per week thereafter). Randomisation was done using interactive response technology and stratified by previous proteasome inhibitor therapy, lines of treatment, and multiple myeloma stage. The primary endpoint was progression-free survival in the intention-to-treat population. Patients who received at least one dose of study treatment were included in the safety population. This trial is registered at ClinicalTrials.gov, NCT03110562 . The trial is ongoing, with 55 patients remaining on randomised therapy as of Feb 20, 2020. Findings: Of 457 patients screened for eligibility, 402 were randomly allocated—195 (49%) to the selinexor, bortezomib, and dexamethasone group and 207 (51%) to the bortezomib and dexamethasone group—and the first dose of study medication was given between June 6, 2017, and Feb 5, 2019. Median follow-up durations were 13·2 months [IQR 6·2–19·8] for the selinexor, bortezomib, and dexamethasone group and 16·5 months [9·4–19·8] for the bortezomib and dexamethasone group. Median progression-free survival was 13·93 months (95% CI 11·73–not evaluable) with selinexor, bortezomib, and dexamethasone and 9·46 months (8·11–10·78) with bortezomib and dexamethasone (hazard ratio 0·70 [95% CI 0·53–0·93], p=0·0075). The most frequent grade 3–4 adverse events were thrombocytopenia (77 [39%] of 195 patients in the selinexor, bortezomib, and dexamethasone group vs 35 [17%] of 204 in the bortezomib and dexamethasone group), fatigue (26 [13%] vs two [1%]), anaemia (31 [16%] vs 20 [10%]), and pneumonia (22 [11%] vs 22 [11%]). Peripheral neuropathy of grade 2 or above was less frequent with selinexor, bortezomib, and dexamethasone (41 [21%] patients) than with bortezomib and dexamethasone (70 [34%] patients; odds ratio 0·50 [95% CI 0·32–0·79], p=0·0013). 47 (24%) patients in the selinexor, bortezomib, and dexamethasone group and 62 (30%) in the bortezomib and dexamethasone group died. Interpretation: A once-per-week regimen of selinexor, bortezomib, and dexamethasone is a novel, effective, and convenient treatment option for patients with multiple myeloma who have received one to three previous lines of therapy. Funding: Karyopharm Therapeutics.